COMPARATIVE CLINICAL AND ANAMNESTIC CHARACTERISTICS OF WOMEN WITH ENDOMETRIAL AND UTERINE CAVITY PATHOLOGY WHO RECEIVED OUTPATIENT AND INPATIENT CARE - Светлана Ивановна Елгина; Юлия Сергеевна Фролова (The Publishing House Medicine and Enlightenment, 2021)
The aim of the research - to conduct a comparative clinical and anamnestic characterization of women with endometrial and uterine cavity pathology who received outpatient and inpatient care. Materials and methods. A retrospective analysis of the management of patients with pathology of the uterine cavity and endometrium in the GAU CO KGKB N 4 and medical institutions of Kemerovo in the period from 2018 to 2020 (according to medical documentation) was carried out. The study included 900 women: group I - 300 women who underwent office hysteroscopy (OGS) in combination with MVA of the uterine cavity, group II - 300 patients who underwent MVA of the uterine cavity, group III - 300 women who underwent inpatient hysteroscopy (CGS) in combination with MVA. Results. When comparing the patients who underwent OHS and GHS, there were no statistically significant differences in age, parity, and gynecological diseases. However, the patients referred to the GHS in medical institutions were more likely to have extragenital pathology. Conclusion. Thus, taking into account the absence of significant differences when comparing the clinical and anamnestic characteristics of patients referred for GHS in a gynecological hospital, the use of invasive interventions at the outpatient stage is possible and justified. The effectiveness of outpatient surgery, namely, visualization, histological confirmation of the pathology of the endometrium and the uterine cavity, requires further study.